1973
DOI: 10.1530/acta.0.0740056
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Corticotrophin Peptides With Homo-Arginine, Lysine or Ornithine Substituted for Arginine in Position 8

Abstract: The steroidogenic and lipolytic activities of corticotrophin-(l-24)-tetracosapeptide and [Lys17.18]corticotrophin-(l-18)-octadecapeptide amide were compared with those of the corresponding analogues variously substituted in position 8 with homo-arginine, ornithine or lysine. Peptides substituted with homo-arginine showed a surprisingly high degree of biological activity; in all the tests performed, the loss o f activity due to the substitution did not exceed a factor of 3 to 10, w hile peptides sub stituted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1973
1973
1988
1988

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Recent studies concerning the relationship between the structure and the function of ACTH (12,27,(34)(35)(36)(37) have shown that the peptide sequences necessary for the binding and for the biological action of this hormone are localized in two distinct parts of the molecule. The C-terminal (ACTH11i-) is important for binding (12) but has no biological action (37) whereas the N-terminal sequence (ACTH1-1o) has a very low binding affinity but is essential for biological action.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies concerning the relationship between the structure and the function of ACTH (12,27,(34)(35)(36)(37) have shown that the peptide sequences necessary for the binding and for the biological action of this hormone are localized in two distinct parts of the molecule. The C-terminal (ACTH11i-) is important for binding (12) but has no biological action (37) whereas the N-terminal sequence (ACTH1-1o) has a very low binding affinity but is essential for biological action.…”
Section: Discussionmentioning
confidence: 99%
“…These pep tides differ not only in the pKa values of these basic and acidic groups, but also in the lengths of their aliphatic chains that carry the basic and acidic groups. Tesser et al 3 ) reported that the presence of a guanidino group in position 8 of the ACTH peptide is essential for the biological activities, but that length of the aliphatic chain carrying the guanidino group is of minor importance. In this study, we showed that replacement of Arg-Glu by Lys-Asp led to a decrease in potency of the lipolytic action and that blocking the free guanidino group of Arg with nitro group resulted in loss of FF A release (Table II).…”
Section: Discussionmentioning
confidence: 99%
“…We suggested that the presence of an OH group at the C-terminus might interfere with binding to appropriate receptors or change the conformation of the peptide. Other workers have reported the importance of a guanidino group in the insulin molecule 2 ) and ACTH molecule 3 ) for biological activities.…”
mentioning
confidence: 99%
“…Compound III was prepared by Kamber (unpublished results). The syntheses of the homoarginine containing reference compounds IV and V have been published elsewhere (Tesser et al 1973a). The syntheses of the corresponding nor¬ arginine peptides VI and VII will be described later (Van Nispen et al, in preparation).…”
Section: Methodsmentioning
confidence: 99%
“…(Desaulles et al 1969) or ornithine (Tesser 8c Schwyzer 1966) is possible, without substantially altering the effects of the peptides. When the same substitutions are made at the active site, the biological potency diminishes drastically (Tesser et al 1973a). The introduction of a substitute closely re¬ lated to arginine, viz.…”
mentioning
confidence: 99%